A Composite Measure for Quality of Care in Patients with Symptomatic Carotid Stenosis Using Textbook Outcome. (October 2020) - Kuhrij, Laurien S.; Karthaus, Eleonora G.; Vahl, Anco C.; Willems, Martine C.M.; Elshof, Jan W.; de Borst, Gert J.; ,; Van den Akker, P.J.; Akkersdijk, G.J.; Akkersdijk, G.P.; Akkersdijk, W.L.; van Andringa de Kempenaer, M.G.; et al.
Abstract : Objective: Composite measures may better objectify hospital performance than individual outcome measures (IOM). Textbook outcome (TO) is an outcome measure achieved for an individual patient when all undesirable outcomes are absent. The aim of this study was to assess TO as an additional outcome measure to evaluate quality of care in symptomatic patients treated by carotid endarterectomy (CEA). Methods: All symptomatic patients treated by CEA in 2018, registered in the Dutch Audit for Carotid Interventions, were included. TO was defined as a composite of the absence of 30 day mortality, neurological events (any stroke or transient ischaemic attack [TIA]), cranial nerve deficit, haemorrhage, 30 day readmission, prolonged length of stay (LOS; > 5 days) and any other surgical complication. Multivariable logistic regression was used to identify covariables associated with achieving TO, which were used for casemix adjustment for hospital comparison. For each hospital, an observed vs. expected number of events ratio (O/E ratio) was calculated and plotted in a funnel plot with 95% control limits. Results: In total, 70.7% of patients had a desired outcome within 30 days after CEA and therefore achieved TO. Prolonged LOS was the most common parameter (85%) and mortality the least common (1.1%) for not achieving TO. Covariates associated with achieving TO were younger age, the absence of pulmonary comorbidity, higher haemoglobin levels, and TIA as index event. In the case mix adjusted funnel plot, the O/E ratios between hospitals ranged between 0.63 and 1.27, with two hospitals revealing a statistically significantly lower rate of TO (with O/E ratios of 0.63 and 0.66). Conclusion: In the Netherlands, most patients treated by CEA achieve TO. Variation between hospitals in achieving TO might imply differences in performance. TO may be used as an additive to the pre-existing IOM, especially in surgical care with low baseline risk such as CEA.